Analysis of Indonesian and Malaysian Pepper Export Competitiveness in the International Market - Wanto, Hary (Research Horizon, 2022)
Indonesia is an agricultural developing country that has abundant natural wealth. Various types of plants can thrive in Indonesia, including food crops, plantations, including spices. Indonesian spice production has been recognized and is well known abroad. Pepper plantations in Indonesia are divided into two types, namely community plantations (PR) and large private plantations. Globalization of trade requires Indonesia to be able to increase the competency of its pepper products so that it can compete in the world. This research method uses a quantitative research method. The type of data in this research uses secondary data, namely data obtained from a research library where the data obtained is in the form of data. The analytical methods used in this research are descriptive methods and quantitative methods. The descriptive method is used to create a picture of the development of pepper exports from Indonesia and its competitor countries, namely Malaysia, while the quantitative method, where data is obtained in the form of numbers and analyzed using statistical and econometric methods, is used to analyze the competitiveness of comparative advantage and competitive advantage. Indonesia has a higher average ISP value and is declared a pepper exporter. Malaysia is still behind in the specialist pepper trade with Indonesia. The development of Indonesian pepper exports is better than Malaysia, in terms of the value of pepper exports to international markets.